Избранные статьи - Белинский Виссарион Григорьевич (Школьная библиотека, 1981)
Экземпляры: (20241212) / Инвентарный номер: 1883 / Цена: 0.20 / Сис.шифр: 83.3(2Рос=Рус)1ст / Авт.знак: Б 43 / ГРНТИ: 17 / ББК: 83.3(2Рос=Рус)1